2009
DOI: 10.1523/jneurosci.0651-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Notation-Independent Representation of Fractions in the Human Parietal Cortex

Abstract: Although the concept of whole numbers is intuitive and well suited for counting and ordering, it is with the invention of fractions that the number system gained precision and flexibility. Absolute magnitude is encoded by single neurons that discharge maximally to specific numbers. However, it is unknown how the ratio of two numbers is represented, whether by processing numerator and denominator in separation, or by extending the analog magnitude code to relative quantity. Using functional MRI adaptation, we n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
106
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 21 publications
(32 reference statements)
9
106
1
1
Order By: Relevance
“…To date, these alternative predictions remain untested. In fact, only two studies have ever probed the neural representations underlying the processing of fractional numbers (Ishebeck et al, 2009;Jacob and Nieder, 2009a), and neither of these assessed the neural representations underlying decimal numbers, or the relationship between neural representations of magnitude across different formats for rational numbers.…”
Section: Using Fmri To Investigate Magnitude Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, these alternative predictions remain untested. In fact, only two studies have ever probed the neural representations underlying the processing of fractional numbers (Ishebeck et al, 2009;Jacob and Nieder, 2009a), and neither of these assessed the neural representations underlying decimal numbers, or the relationship between neural representations of magnitude across different formats for rational numbers.…”
Section: Using Fmri To Investigate Magnitude Representationmentioning
confidence: 99%
“…Jacob and Nieder (2009a) used an adaptation paradigm to test symbolic fraction magnitudes (single and multi-digit fractions). Recovery in the BOLD signal after habituation was observed in the frontoparietal cortex, and specifically the IPS.…”
Section: Using Fmri To Investigate Magnitude Representationmentioning
confidence: 99%
“…For example, using an fMRI, Piazza, Izard, Pinel, Bihan, and Dehaene (2004) demonstrated that different symbolic formats activate an abstract quantity representation in the hIPS. In addition, fMRI research has also found that multiple numerical formats activate the same IPS area (Jacob & Nieder, 2009;Piazza, Pinel, Bihan, & Dehaene, 2007). In contrast, fMRI research has found that quantity representations appear to be format dependent in both the left (Cohen Kadosh, Muggleton, Silvanto, & Walsh, 2010;Cohen Kadosh et al, 2007) and right (Cohen Kadosh et al, 2010) parietal lobes.…”
Section: Numerical Cognition Architecturesmentioning
confidence: 99%
“…Studies with behaviorally trained monkeys have identified a parieto-frontal network of individual neurons selectively tuned to the number of items. This cortical network is putatively homologous with the network endowing humans to estimate numerosity, count, and operate with number symbols (5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%